The Role of Traditional Games on Children's Ground Motor and Emotional Ability (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2022)
Abstract. Traditional game is one of the sport activity which has many benefits for body health, psychic, and the surrounding environment such as cultural values that must be preserved. Teaching traditional games to children is very necessary at this time to train their motor and social emotional. The writing method starts from problem identification, literacy study, data analysis, building alternative problem solving, and conclusion. Chracters who formed through traditional games walking unconsciously, and this is which makes children learn with it self without coercion. That’s why traditional games are necessary returned to the main game for children so that children can be created strong character and become the nation’s generation who have high integrity and good characteristic. In conclusion The introduction of traditional games in children is very important and can affect the growth and development of children through motor and social emotional conditions.